Trade Liberalization and Integration of Domestic Output Markets in Brazil - Reis, Jose Guilherme (World Bank, Washington, DC, 2018)
This paper describes how different policy distortions have been impeding better integration of Brazil's external and internal product markets and discusses how these distortions have prevented domestic firms from benefiting from multiple sources of efficiency gains. The paper first focuses on the costs of barriers to global integration, followed by an overview of policy induced stringencies hampering domestic integration. Drawing from general and partial equilibrium analyses, the paper also provides evidence of potential impacts of removing some of those distortions and discusses policy options to promote better allocation of resources across the economy. The main conclusion of the paper is that Brazil could gain significantly from opening to foreign trade. Yet, for Brazil to take full advantage of the opportunities that external integration offers, domestic markets also need to function better, so it is key to ensure that the removal of external barriers to integration is coordinated with the removal of internal distortions to domestic market integration.